Double exposures: Embodiment, vulnerability and agency in Letizia Battaglia's photography. Issue 3 (1st June 2021) - Karagoz, Claudia
Letizia Battaglia is best known for her photojournalistic work during the 1970s and 1980s, when she assembled a vast archive of images of Mafia victims and perpetrators and of poor Sicilians. In recent years, she has created captivating new photographs named Re-elaborations. These works combine in a single frame her historic photographs of Mafia violence with new subjects ‐ women, children and nature. This article investigates how Battaglia's earlier and new photographs have succeeded in raising awareness about Mafia violence. Engaging with gender and visual theory, the article shows how these works offer compelling narratives of violence and poverty that capture the attention of viewers, involve them in the construction of meaning and prompt empathetic reactions. Despite having received many international awards, only recently has Battaglia's work been recognized with significant retrospectives in Italy. No major studies on her work have been produced to date, and her recent photographs have received scarce critical attention. This article intends to fill that lacuna, enrich existing conversations on the artist and foster future investigations of her work.